PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA SEKOLAH DASAR - Siti Naurah Laila Rasyidah; Stefany Putri Ariana; Juhana Sakmal; Engga Dallion (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to find out how to apply the contextual teaching and learning model in improving elementary school students' science learning outcomes. This research uses descriptive qualitative methods with literature study techniques. Data collection techniques are carried out by searching for scientific articles related to research. The Contextual Teaching and Learning (CTL) model is learning that links learning material to real-world situations through direct student involvement. Based on data from 12 journal articles that have been analyzed, it can be concluded that the Contextual Teaching and Learning learning model can have a positive influence on student learning outcomes in Natural Sciences subjects at high grade level.